2016
DOI: 10.3892/mmr.2016.5061
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of Wnt signaling component, secreted frizzled-related protein 3 in astrocytoma and glioblastoma

Abstract: Secreted frizzled-related protein 3 (SFRP3) is a member of the family of soluble proteins, which modulate the Wnt signaling cascade. Novel research has identified aberrant expression of SFRPs in different types of cancer. In the present study the expression intensities and localizations of the SFRP3 protein across different histopathological grades of astrocytic brain tumors were investigated by immunohistochemistry, digital scanning and image analysis. The results demonstrated that the differences between exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
14
1
Order By: Relevance
“…β-catenin stabilization results in β-catenin translocation into the nucleus, followed by increased expression of proliferation-related genes (23). As SFRPs and Wnt proteins exhibit high homology in their cysteine-rich domains, SFRPs, including SFRP5, can compete with the frizzled receptor to bind Wnt ligands and regulate the canonical and non-canonical Wnt signaling pathways (24)(25)(26). In the present study, it was observed that SFRP5 attenuated β-catenin expression in SMCs.…”
Section: Discussionsupporting
confidence: 51%
“…β-catenin stabilization results in β-catenin translocation into the nucleus, followed by increased expression of proliferation-related genes (23). As SFRPs and Wnt proteins exhibit high homology in their cysteine-rich domains, SFRPs, including SFRP5, can compete with the frizzled receptor to bind Wnt ligands and regulate the canonical and non-canonical Wnt signaling pathways (24)(25)(26). In the present study, it was observed that SFRP5 attenuated β-catenin expression in SMCs.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, the identification of novel molecular targets responsible for tumour progression and biomarkers for prediction of disease outcome and response to treatment is extremely requisite. Several novel studies indicate the involvement of Wnt signalling in the molecular pathogenesis of glial tumours . However, very little is known about the possible association of the proteins involved in the Wnt pathway with tumour malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is still not possible to define the exact number and chronology of changes during gliomagenesis, they found that key genes responsible for the formation and progression of astrocytic brain tumours are most frequently involved into deregulated oncogenic pathways: RTK/RAS/PI3K, TP53 and RB . Recent studies have shown that altered signal transduction in Wnt signalling pathway is also involved in the molecular pathogenesis of glial tumours …”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that sFRP2 acted as an antagonist of Wnt5a mediating the progression of glioblastoma and breast cancer. A recent study in immunohistochemistry revealed that the expression level of soluble frizzled-related protein 3 (sFRP3) was decreased in the nucleus in higher grade astrocytoma, indicating the antagonistic ability of Wnt signaling ( 34 ). Further studies are needed to decipher whether sFRP2 and sFRP3 function in a common pathway or in parallel pathways to block Wnt5a signaling.…”
Section: Discussionmentioning
confidence: 99%